2011
DOI: 10.1016/j.ijscr.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in the canal of Nuck hydrocele: An unusual presentation

Abstract: The authors describe an unusual rare presentation of endometriosis in a hydrocoele of the canal of Nuck. A 43-year-old lady presented with a swelling in her right groin associated with mild discomfort. Examination revealed a cystic swelling in the groin for which she underwent an exploration and excision of the swelling. Surgery revealed a hydrocele of the canal of Nuck which was confirmed histologically. The unusual presentation of endometriosis in the sac was confirmed immunocytochemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Some patients with endometriosis in the inguinal region have been reported. 11,12 The patent canal of Nuck supports the theory of retrograde implantation or movement of endometrial tissue into the inguinal canal. 13,14 When a cystic mass contains inguinal endometriosis, it should be differentiated from hydrocele of the canal of Nuck.…”
Section: Discussionmentioning
confidence: 82%
“…Some patients with endometriosis in the inguinal region have been reported. 11,12 The patent canal of Nuck supports the theory of retrograde implantation or movement of endometrial tissue into the inguinal canal. 13,14 When a cystic mass contains inguinal endometriosis, it should be differentiated from hydrocele of the canal of Nuck.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that IEM can form at various sites including hernia sacs [7][8][9][10][11][12][13], Nuck's canal [14][15][16][17], the round ligament [3-7, 13, 18-22], and groin skin [23]. However, because most of these are case reports, the clinical characteristics associated with the site of IEM occurrence and the optimal diagnostic or therapeutic strategies have not been compared.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 studies (18 case reports and 2 case series), which comprised 36 patients who were diagnosed with an endometriotic lesion arose in the NC, were finally considered eligible for inclusion in the qualitative analysis of the present systematic review [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%